Asymptomatic throat carriage rate and antimicrobial resistance pattern of Streptococcus pyogenes in Nepalese school children - Dumre, SP; Sapkota, K; Adhikari, M; Acharya, D; Karki, M; Bista, S; Basnyat, SR; Joshi, SK (Kathmandu University Medical Journal, 2010)
Background: Streptococcus pyogenes or Group A streptococcus (GAS) causes several suppurative and non suppurative infections. In addition to pharyngitis and skin infections, GAS are also the causative agent of post-streptococcal infection syndromes such as acute rheumatic fever (ARF) and post-streptococcal glumerulonephritis (PSG). GAS frequently colonises in the throat of an asymptomatic person. Pharyngeal carriage rates of GAS among healthy school children vary with geographical location and seasons. Objectives: We carried out this preliminary study to determine the throat carriage rate and antimicrobial resistance trend of Streptococcus pyogenes or Group A streptococcus (GAS) among the Nepalese school children. Materials and methods: Four schools situated at different locations of Kathmandu valley were included in the study. Throat swabs from 350 students of age group 5-15 years were collected, immediately transported to the laboratory and were processed for S. pyogenes following standard microbiological procedures. Antimicrobial susceptibility testing of the isolates was performed by Kirby Bauer disc diffusion method following CLSI guidelines. Results: S. pyogenes was isolated from 10.9% (38/350) of the screened children. The GAS colonisation rate was statistically insignificant (P>0.05) with sex and age sub-groups, although the rate was slightly higher among girls and age sub-group 9-12 years. No significant difference in carrier rate was observed among different schools (P>0.05). All isolates were susceptible to azithromycin. No resistance was detected for penicillin and its derivative antibiotic ampicillin. Highest resistance rate was observed for cotrimoxazole (71.0%) followed by chloramphenicol (7.8%), ciprofl oxacin (5.2%) and erythromycin (5.2%). Conclusion: Antibiotic resistant GAS isolated from asymptomatic Nepalese school children is a public health concern. When screened and appropriately treated with antibiotics, carriers can be prevented from spreading of streptococcal infections in the school environment and the community. Preventing cross infections would ultimately reduce the incidence of life-threatening sequelae which are debilitating and difficult to treat. It is recommended to conduct regular screening and GAS surveillance in schools, and maintain rational use of antibiotics to minimise GAS carriage/infections and resistance. Key words: Streptococcus pyogenes; Antibiotics Resistance; Throat carriage; Children; Nepal. DOI: 10.3126/kumj.v7i4.2760 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 392-396